Legal issues the insurance market (Journal of actual problems of jurisprudence, 2019)
In the state is considered the legal issues of the insurance market. And the legal status of their members.Insurance market, the insurance market – part of the financial market, which offers insurance services.Insurance services in this market offer insurance company. One of the key principles of the organization ofthe insurance market is to ensure fair competition, the insurance companies.Keywords: insurance, compulsory insurance, insurance relations, insurance companies.